Polinização da abóbora (Curcubita moschata D.) pela abelha Arapuá (Trigona spinipes): requerimentos da cultura e eficiência do polinizador - Mélo, Diogo de Barros Mota (2010)
This work was aimed at studying the pollination requirements of pumpkin (Curcubita moschata D.) jacarezinho variety, its flower visitors and potential pollinators of this culture. The study was conducted from October 2009 to February 2010, at the Agriculture I sector of Instituto Federal de Alagoa of Campus Satuba, city of Satuba-AL. The pumpkin crop was established following all cultural practices to lead the culture and was intercropped with banana (Musa acuminata). The planted area had 0.3 hectares, with 500 plants. To determine the requirement for pollination studied the efficiency of open pollination, manual cross-pollination and restricted pollination. Floral visitors were collected randomly in different plants 10 minutes every hour, from 05 a.m. to 12 a.m.. It was also evaluated the pollination efficiency of the main pollinators. For the analysis of characteristics (height, weight, number of seeds, polar and equatorial circumference) of fruit produced according to the type of treatment were analyzed using analysis of variance, through the Program SISVAR, adopting a significance level of 5 %. Trigona spinipes and Apis mellifera were the most frequent visitors, with a greater frequency of visits from 6 a.m. to 9 a.m.. All species of visitors foraging nectar. The flowers Curcubita moschata which received no visits weren’t fruitful. The flowers that received treatment manual cross-pollination had fewer fruit set compared with restricted pollination, indicating a possible deficit of pollen grains deposited on its stigma. But in relation to fruit quality manual cross pollination was as effective as the open-pollinated. To study the efficiency of pollinator Trigona spinipes it was checked the settlement of fruit after one, two, three and four visits. There was statistically significant difference (P <0.05) of fruit set in relation to the number of visits. But there was no significant difference (P <0.05) on weight compared with the number of visits the greater was the number of visits, the greater the number of seeds, height and circumference both polar and equatorial (P <0.05). However there was no significant difference (P <0.05) in the number of seed and the height after the third visit and circumference (equatorial and polar) after the second visit. The work showed that the pumpkin is highly dependent on biotic pollinators; Trigona spinipes which is the main pollinator of the crop in the study area and in the range of one to four visit of Trigona spinipes, the higher the number, the higher the fruit set and fruit quality.